2008
DOI: 10.3748/wjg.14.6036
|View full text |Cite
|
Sign up to set email alerts
|

Decreased phagocytic activity of Kupffer cells in a rat nonalcoholic steatohepatitis model

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 28 publications
4
41
0
Order By: Relevance
“…Although these models lack obesity and insulin resistance, two major characteristics of NASH in humans, the possible relation of Kupffer cells with inflammation, steatosis, and fibrosis may resemble the human NASH. We also demonstrated decreased Kupffer cell phagocytic activity in this model [27] . The possible Kupffer cell dysfunction characterized by decreased phagocytic activity and increased cytokine production should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 64%
“…Although these models lack obesity and insulin resistance, two major characteristics of NASH in humans, the possible relation of Kupffer cells with inflammation, steatosis, and fibrosis may resemble the human NASH. We also demonstrated decreased Kupffer cell phagocytic activity in this model [27] . The possible Kupffer cell dysfunction characterized by decreased phagocytic activity and increased cytokine production should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 64%
“…Namely, it has been considered to represent the phagocytic activity of KCs. However, recent studies have reported that impairment of KC phagocytic activity is dependent on the level of activity in each KC and is not dependent on a reduction in the total number of KCs in studies of animal models of non-alcoholic steatohepatitis (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Kupffer cells, part of the innate immune system, produce various cytokines and are known to play a role in pathologies of the liver [2,3] . Abnormally functioning Kupffer cells are suspected to be involved in NASH [4] . Although the etiological mechanisms of NASH have not been fully elucidated, similar histopathological findings in NASH and alcoholic hepatitis suggest the existence of a common underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%